2015
DOI: 10.1021/acs.biochem.5b00930
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Substrate Access Portal of 5-Lipoxygenase

Abstract: The overproduction of inflammatory lipid mediators derived from arachidonic acid contributes to asthma and cardiovascular diseases, among other pathologies. Consequently, the enzyme that initiates the synthesis of pro-inflammatory leukotrienes, 5-lipoxygenase (5-LOX), is a target for drug design. The crystal structure of 5-LOX revealed a fully encapsulated active site, thus the point of substrate entry is not known. We asked whether a structural motif, a “cork” present in 5-LOX but absent in other mammalian li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…This observation suggests that either these concealed amino acids interact with the lipid bilayer or that the impaired nuclear translocation is a consequence of a conformational change provoked by a mutation that is incompatible with membrane binding. Although we cannot eliminate the second possibility, the same substitutions were not destabilizing in the Stable‐5‐LOX (20). Moreover, there is substantial precedent for membrane anchoring of proteins by the insertion of aromatic amino acid side chains into the bilayer.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This observation suggests that either these concealed amino acids interact with the lipid bilayer or that the impaired nuclear translocation is a consequence of a conformational change provoked by a mutation that is incompatible with membrane binding. Although we cannot eliminate the second possibility, the same substitutions were not destabilizing in the Stable‐5‐LOX (20). Moreover, there is substantial precedent for membrane anchoring of proteins by the insertion of aromatic amino acid side chains into the bilayer.…”
Section: Discussionmentioning
confidence: 93%
“…Y181 was additionally replaced by Phe to investigate the possibility that the hydroxyl group of Y181 provides an H bond necessary for catalysis. It has been reported that in the context of Stable‐5‐LOX, neither F177A, Y181A, nor F177/Y181A mutations destabilize the enzyme and do not adversely affect the basal levels of 5‐H (p)ETE production of purified 5‐LOX (in the absence of cellular regulatory cofactors) (20). Expression of 5‐LOX and FLAP in each of the HEK293 cell lines was verified by immunoblotting, with normalization to β‐actin ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CAPE ( 2 ) (−8.8 kcal/mol) formed a hydrogen bond with Leu 420 (OH ··· O: 3.07 Å) and a π‐π interaction with His372. Compound 7 (−8.9 kcal/mol) underwent pi‐pi interactions with His367 and was the only tested ligand that showed a π‐π interaction with Phe177 which may play a part in product specificity . Compounds 9 (−8.7 kcal/mol) and 10 (−8.7 kcal/mol) had pi‐pi interactions with His 372.…”
Section: Resultsmentioning
confidence: 99%